2019
DOI: 10.1016/j.jaci.2019.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Functional evaluation of the pathological significance of MEFV variants using induced pluripotent stem cell–derived macrophages

Abstract: O. N. Atkas declares no relevant conflicts of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 20 publications
6
22
0
Order By: Relevance
“…We previously demonstrated that such MLs can be used to model the proinflammatory phenotypes of various autoinflammatory disorders [14,[28][29][30]. Combined with the current study, which successfully identified candidate compounds, we concluded that this ML-based HTS system provides a versatile platform for screening candidate compounds for treating autoinflammatory disorders.…”
Section: Discussionsupporting
confidence: 64%
“…We previously demonstrated that such MLs can be used to model the proinflammatory phenotypes of various autoinflammatory disorders [14,[28][29][30]. Combined with the current study, which successfully identified candidate compounds, we concluded that this ML-based HTS system provides a versatile platform for screening candidate compounds for treating autoinflammatory disorders.…”
Section: Discussionsupporting
confidence: 64%
“…MLs can be used to model the pro-inflammatory phenotypes of various autoinflammatory disorders. 14,[29][30][31] Combined with the current study, which successfully identified candidate compounds, we concluded that this ML-based HTS system provides a versatile platform for screening candidate compounds for treating autoinflammatory disorders.…”
Section: Discussionsupporting
confidence: 55%
“…We used MLs established from PSCs for the HTS, because MLs are easy to propagate, freeze‐stock, and differentiate into functional macrophages or dendritic cells 15 . We previously demonstrated that such MLs can be used to model the pro‐inflammatory phenotypes of various autoinflammatory disorders 14,29‐31 . Combined with the current study, which successfully identified candidate compounds, we concluded that this ML‐based HTS system provides a versatile platform for screening candidate compounds for treating autoinflammatory disorders.…”
Section: Discussionmentioning
confidence: 55%
“…Two main approaches are used to create iMph-based disease models: (i) generating iMphs from patient-derived iPSCs and (ii) introducing disease-associated mutations to iPSCs derived from healthy donors followed by the generation of iPSC-derived iMphs. The first approach has successfully been used to model Gaucher disease, Tangier disease, familial Mediterranean fever, chronic granulomatous disease (CGD), early onset sarcoidosis, Alzheimer disease, Parkinson disease, and others ( Panicker et al, 2012 ; Brault et al, 2014 ; Zhang et al, 2015 ; Aflaki et al, 2016 ; Haenseler et al, 2017 ; Takata et al, 2017 ; Brownjohn et al, 2018 ; Takada et al, 2018 ; Shiba et al, 2019 ; Mukhopadhyay et al, 2020 ). In the second approach, the introduction of p47-ΔGT mutation allowed to model CGD ( Klatt et al, 2019 ), and iMphs bearing genetic KOs of IL-10RA, IL-10RB, STAT1, or STAT3 modeled the very-early onset bowel disease (VEOBD) ( Mukhopadhyay et al, 2020 ; Sens et al, 2020 ).…”
Section: Imph Applications and Prospectsmentioning
confidence: 99%